Preoperative medication for glaucoma and cataract: problems of choice - A. A. Gusarevich; Yu. A. Gamza (Сибирский научный медицинский журнал, 2020)
There have been multiple scientific publications reporting of cases and post-hoc analysis of relationship between the prostaglandin analogues (PA) use and postoperative macular edema development in patients underwent cataract surgery. The purpose of research is to compare effects of different groups of antihypertensive drugs on condition of central retina in patients with primary open-angle glaucoma (POAG) after phacoemulsification of cataract (PC) and combined surgeries for cataract and glaucoma. Material and methods. Analysis was carried out with data on 36 patients (49 eyes) underwent the cataract surgery on the top of POAG: group I – 12 patients (15 eyes) who were receiving antihypertensive therapy of PA before and after PC; group II – 10 patients (11 eyes) who were receiving PA therapy prior to combined surgery for cataract and glaucoma (PA were cancelled during postoperative period); group III – 14 patients (25 eyes) who were receiving antihypertensive therapy of any drug group excluding PA before and after PC. Results. The thickness in central retina of all 3 groups` patients was comparable both before and after the surgery, differences were statistically insignificant. Cross-group measurement results were also statistically insignificant. Conclusion. Findings of the study have not identified any convincing evidence that would support a change of antihypertensive drugs against POAG as a preparation for cataract surgery and during early postoperative period to reduce the risk of macular edema. The use of prostaglandins analogs does not result in conspicuous changes in thickness of macula zone of retina during postoperative period.